Incorporating sustainable development and inclusive education in teacher education for the Arctic - Windsor, Sally; Maxwell, Gregor Ross; Antonsen, Yngve (Polar Geography, 2022)
This article explores how teacher education institutions can better prepare teachers to help to create inclusive and sustainable self-determined Arctic communities. Building on the theoretical concepts of just sustainabilities, transgressive learning, the capabilities approach, and relational thinking within inclusive pedagogy, we propose that education for sustainable development (ESD) and inclusive education (IE) be more centrally situated across curriculum areas for all new teachers. To achieve this in practice, we suggest that teacher education programs need to better prepare new teachers to engage in critical participatory action research that empowers them to collaborate with Arctic communities.